Establishment of an effective enterprise in the touristic market - R. Fakhrutdinova, Liliya (2018)
In this paper, the authors describe the creation of an effective enterprise in the field of tourism. In order to create an effective tourist agency, it is necessary to understand the mechanism of the tourism market in general and the role of travel agencies and tour operators, in particular. Business in the tourism industry is fairly good because it is possible to open a tourist agency with the least investment and without the experience of such activities. This activity is not licensed in any way, and there is no need for permits for this reason. At the same time, competition in the tourism business is quite high, and the need for servicing travel agencies in the circumstances of the crisis naturally decreases. It is necessary to choose the direction of activity being guided by one's own interests, skills of hired personnel or general market trends. Then you need to choose one of the development models (independent travel agency, travel agency based at home, franchise or online travel agency). You can consider already later the registration aspects, organization of your office, software, the creation of a website, the selection of employees and partners, tour operators, as well as advertising. It is also necessary to choose the direction of activity being guided by one's own interests, skills of hired personnel or general market trends. It is necessary to attract buyers with high-quality service, to cooperate only with reliable tour operators - to form an image that will in future become functional for you.